PROBLEMS OF USING FACE IMAGE SEGMENTATION, IDENTIFICATION, FILTERING, FACIAL SIGNS DISTRIBUTION CRITERIA IN DETERMINING PERSONAL BIOMETRIC CHARACTERISTICS (World Bulletin of Management and Law, 2022)
In this article, using the possibilities of today's information and communication technologies (ICT), scientific researches focused on this field, such as collecting data on the facial image based on the biometric characteristics of the person, processing the facial image, converting it to a digital image, segmentation, identification, filtering, distinguishing facial features the results of extensive analysis of their work are presented